Thermal Characteristics of Mozzarella Cheese Product (Study on Citric Acid Concentration) - Komar, Nur; Hawa, La Choviya; Prastiwi, Rika (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
Mozzarella cheese is soft cheese that is not fully ripened, or usually called fresh cheese. The making of Mozzarrella cheese needs long time. The making of cheese can be performed by direct acidification, therefore this step does not have to wait culture work of bacterial starter to produce lactic acid. The method used in this research is direct acidification using citric acid as the acidifier. This research was objected to know the effect of citric acid concentration on chemical and physical characteristics, and to determine thermal conductivity of mozzarella cheese. This research used deterministic method that assisted by empirical data to express the physical, chemical, and thermal properties. Experimental method was used with 3 level of citric acid concentration i.e. 0.12, 0.16 and 0.20% based on 25 liter of fresh cow milk. Each variation was assessed once for chemical parameters including moisture content, yield, and thermal conductivity (k). Thermal conductivity was analyzed using heat transfer theory that solved by numeric method implicitly. The steps of the research included functional tool desigining, mozarella cheese making, and determination of thermal conductivity. The result showed that the highest yield of mozzarella cheese was 7.789% at 0.16% of citric acid. The highest density was 1194.631 kg/m3 at 0.20% of citric acid. The highest protein content was 29.299% at 0.12% of citric acid, and the highest fat content was 13.121% at 0.16% of citric acid. The highest water content was 45.204% at 0,16% of citric acid. The highest heat value was 2721.400 J/kgoC at citric acid concentration of 0.16%. The highest thermal diffusivity value is 3.730 x10-7 m2/s at 0.12% of citric acid. The average of thermal conductivity value at 0.12% of citric acid concentration was 1.165 W/moC, at 0.16% was 0.539 W/moC, and at 0.20% was 0.634 W/moC. The equations of thermal conductivity were k = 34.944 – 0.493 X1 -0.0102 X2 and = 19.566 x10-6- 0,0025 X1 – 0,4304 X2.Keywords: mozzarella cheese, citric acid, thermal conductivity